Well-being and Workplace Performance: A case of corporates in the region of Larache, Morocco - EL HASSANI , Hajar; EL ALLAOUI , Bilal; TIJANI , Omar (Revue Internationale des Sciences de Gestion, 2023)
Purpose: this paper sheds light on the positive association between people’s well-being as an explanatory variable and work performance as a response variable. Based on the analysis and processing of data related to eight companies, using a quantitative method as part of an inter- pretivism epistemological position, we intended to seek how improving the state of well-being could increase work performance. Design/methodology/approach: The survey data were collected from eight companies; seven are operating in the food industry and one in the metallurgy industry whose staff number ex- ceeds 300 employees. The collected data were processed and analysed using a quantitative method as part of an interpretivist epistemological trend. Findings: The empirical results indicate that a good state of well-being is a key factor in work performance. The social context is, in contrast, the most influential element when it comes to well-being; hence, strengthening employees’ relationships at work is a facilitator of well-being. However, companies are still late in terms of capitalizing on well-being measures/indicators even though there is awareness about the importance of well-being for work performance. Originality/Value: This study highlights the association between employees’ well-being and work performance. By bringing that study down to the ground of Larache-Morocco, it allows researchers to conquer a new fertile zone.